Gross morphology and ultrastructure of the female reproductive system of Diaphorina citri (Hemiptera: Liviidae) - Fabio Cleisto Alda Dossi; Fernando Luis Cônsoli (Zoologia (Curitiba), 2014)
The morphological traits of the female reproductive system of Diaphorina citri were examined in detail. Diaphorina citri has telotrophic ovaries with ovarioles organized as a "bouquet", displaying a rudimentary terminal filament and a syncytial tropharium. The vitellarium carries a single growing oocyte at each maturation cycle, which is connected with the tropharium by a nutritive cord. Morpho-functional changes occur during oocyte development, mainly during mid to late vitellogenesis. Morphological events such as the patency of the follicular cells and the intense traffic of vesicles through para- or intracellular processes, suggest a possible route for endosymbiont invasion of D. citri reproductive tissues. Similar events have been demonstrated to be involved in the process of ovariole invasion by endosymbionts in other sternorrhynchans that share reproductive traits with psyllids.